Enhancing Project Delivery in Gaindakot Municipality, Nepal, Through the Bromilow Time-Cost Model: A Strategic Mitigation Approach - Kandel Shankar; Sigdel Sandesh (Baltic Journal of Real Estate Economics and Construction Management)
Construction projects rely on the precise interplay of time and cost to achieve success. This study explores this critical relationship, exploring how contract size influences these vital metrics and proposes data-driven mitigation strategies to ensure projects resonate with optimal performance. This study employs Bromilow’s time-cost model to investigate the relationship between project duration and expenditure. A statistically significant positive correlation was found, with a linear regression model showing a strong association (R² = 0.836) between the two variables. The analysis also reveals a more detailed role for contract size, suggesting a potentially limited influence on time and cost variations. Several factors can disrupt the harmony of project execution, thereby impeding its performance concerning both cost and time. Key factors contributing to this disruption include the unreliability of contractors, inadequacies in site management, breakdowns in communication channels, delays in decision-making processes, and constraints within budgetary allocations. The identification and subsequent mitigation of these diverse challenges emerge as pivotal tasks in ensuring the smooth arrangement of project endeavours. Bromilow’s model provides a path to a more harmonious performance. It unveils a logarithmic correlation between project cost and duration, indicating a constant value of 24.35 days for projects exceeding one million Nepalese rupees (NPR). This underscores the substantial influence of project scale on time, emphasizing the necessity for management approaches based on project size. To achieve a truly masterful performance, the study advocates for a holistic management approach. This includes proactive decision-making, establishing clear and effective communication channels that resonate with all stakeholders, and maintaining meticulous financial oversight to ensure accurate budgeting and efficient resource allocation. By implementing these strategies, project teams can navigate the complexities of construction with greater ease, optimizing both time and cost performance. Ultimately, they can turn projects into symphonies of success, ensuring their completion on time, within budget, and to the highest quality.